The planned development’s effect on the performance in ice hockey - Géczi, Gábor; Velenczei, Attila; Nagy, Attila; Bognár, József (Applied Studies in Agribusiness and Commerce, 2013)
The sports are growing everywhere in the world, so there is no other way to maintain or to increase the level of quality just the strategic planned development (GÉCZI, 2012), because thousands of specialist are working hardly on the better results worldwide. The aim of this study was to monitor the ice hockey players’ physical development in Hungary since 2007, focusing the results after opening the federations’ Methodical Center (MC). One can see a remarkable development during the last years in the domestic ice hockey, which is perceptible following the sport performance and results. The first step of the planned development was the reform of the curriculum in the coaches courses (from 2004 continuously) at every level, the second step was the opening our MC in 2010, where the Hungarian players and experts (coaches and officials) can develop their skills and their knowledge about the ice hockey. We examined the effect of the above mentioned procedures, comparing the national try-out test running events (10 m, 60 m, 6×9 m, 400 m, 1500 m) by the best twenty U18 players (N=80). According to the opening of the Methodical Center, we used the data from 2012, 2009, 2008 and 2007.